2020
DOI: 10.52958/iftk.v16i3.2010
|View full text |Cite
|
Sign up to set email alerts
|

Perancangan Chatbot Sebagai Pembelajaran Dasar Bahasa Jawa Menggunakan Artificial Intelligence Markup Language

Abstract: Bahasa Jawa merupakan salah satu bahasa daerah yang digunakan di Indonesia. Masyarakat Indonesia suku Jawa yang tinggal di luar provinsi Jawa Tengah, provinsi DI Yogyakarta dan provinsi Jawa Timur jarang atau bahkan tidak menggunakan bahasa Jawa. Penutur bahasa Jawa saat ini juga sedang menurun seiring dengan perkembangan teknologi. Jika kejadian ini terus terjadi ada kemungkinan suatu saat nanti bahasa Jawa dilupakan karena pelestarian bahasa Jawa sudah berkurang. Oleh karena itu, penulis ingin membuat media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
5
0
3
Order By: Relevance
“…For example, chatbots have the potential to be used as a means of learning Chinese: Chen got positive results for Chinese vocabulary learning with a chatbot [23]. We found as well examples for Javanese [24], Acehnese [25], and Arabic [26], Malaysian [27].…”
Section: Current Use Of Chatbots In General Language Learning and The...mentioning
confidence: 83%
See 2 more Smart Citations
“…For example, chatbots have the potential to be used as a means of learning Chinese: Chen got positive results for Chinese vocabulary learning with a chatbot [23]. We found as well examples for Javanese [24], Acehnese [25], and Arabic [26], Malaysian [27].…”
Section: Current Use Of Chatbots In General Language Learning and The...mentioning
confidence: 83%
“…There are different methods how chatbots work and are developed. Generally, the way a chatbot works starts from the user inputting a word or sentence, then the system on the chatbot selects the data in the dataset and then presents it to the user as an answer output [24].…”
Section: Technical Basics Of Chatbots and Development Gramabot For Le...mentioning
confidence: 99%
See 1 more Smart Citation
“…In research conducted on Psychology students at Universitas Sarjanawiyata showed that the use of AI-based applications such as Netflix and Joox Music can significantly and effectively improve students' listening skills [21]. In addition, AI can also take the form of chatbots that facilitate communication, to improve one's language skills [22]. Then, in other studies, the use of AI was shown to improve writing skills and lower the fear of writing [23].…”
Section: Discussionmentioning
confidence: 99%
“…Terdapat pula sejumlah penelitian tentang penerapan chatbot sebagai media pembelajaran yang menjadi urgensi PKM ini. Seperti pada temuan (Abilowo et al, 2020) yang mengungkapkan bahwa implementasi chatbot sebagai bahan ajar bahasa jawa terbukti dapat berfungsi sesuai yang diharapkan dan tingkat akurasinya mencapai 90%. Senada dengan temuan (Sarosa et al, 2020) yang menyatakan bahwa hasil uji efektivitas chatbot sebagai bahan ajar bahasa inggris sebesar 97,5%.…”
Section: Pendahuluanunclassified